Living with voters’ existential angst - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2013)
SMU Assistant Professor of Law and NMP Eugene Tan analysed the results of the Punggol East by-election and discussed what it signals next for the People’s Action Party (PAP), the Workers’ Party, the opposition in general and Singaporeans. He said that while we should be careful not to extrapolate the results of the Punggol East by-election as being a barometer of national sentiment, the results are nonetheless a useful snapshot of the dynamic political situation. He added that PAP urgently needs to connect more with this existential angst, anxiety and aspirations of voters who feel a growing sense of alienation. Doing so would require a more fundamental rethink of long-standing policies such as immigration. Also, the question was not whether Singapore would see more political plurality, but when that would come about. The PAP could opt to be the responsible steward of that development or it can have change forced upon it.